2007
DOI: 10.2172/926965
|View full text |Cite
|
Sign up to set email alerts
|

Soil-to-Plant Concentration Ratios for Assessing Food Chain Pathways in Biosphere Models

Abstract: This report describes work performed for the U.S. Nuclear Regulatory Commission's project Assessment of Food Chain Pathway Parameters in Biosphere Models, which was established to assess and evaluate a number of key parameters used in the food-chain models used in performance assessments of radioactive waste disposal facilities. Section 2 of this report summarizes characteristics of samples of soils and groundwater from three geographical regions of the United States, the Southeast, Northwest, and Southwest, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…Investigations by Napier et al (2007; have indicated that regionally-distinct soil types can have a significant difference in root uptake by equivalent vegetation. The recent IAEA compendium provides some information for sand, loam, and clay type soils, but the information is sparse and frequently unavailable.…”
Section: Plant/crop Factorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Investigations by Napier et al (2007; have indicated that regionally-distinct soil types can have a significant difference in root uptake by equivalent vegetation. The recent IAEA compendium provides some information for sand, loam, and clay type soils, but the information is sparse and frequently unavailable.…”
Section: Plant/crop Factorsmentioning
confidence: 99%
“…Most measurements are for Sr, Cs, and I. Napier et al (2007; investigated Tc, Pu, Am, Np, and I in three soils of potential importance to nuclear waste disposal scenarios in an attempt to expand the available information for potatoes and onions, but no other root crops.…”
Section: Plant/crop Factorsmentioning
confidence: 99%
See 3 more Smart Citations